THE PRACTICAL BASES OF USING AND TRANSLATING IDIOMS: Irisboyeva Muxlisa, Salomat Boboqulova - Place of work/study: Uzbekistan state world languages university, Irisboyeva Muxlisa; Place of work/study: Uzbekistan state world languages university, Salomat Boboqulova (Лучшие интеллектуальные исследования, 2024)
This article explores the significance of utilizing and translating idiomatic expressions into the English language. Idiomatic expressions consist of words with specific meanings that may not directly relate to the meanings of their individual components. They enrich our speech by adding sensitivity and vibrancy. Despite potential grammatical inaccuracies in their structure, idioms convey precise meanings. Additionally, learners often compare English idiomatic expressions with their equivalents in their native language, such as Uzbek